Generalized Intense Pruritus During Canagliflozin Treatment: Is it an Adverse Drug Reaction? - Vasapollo, Piero; Cione, Erika; Luciani, Filippo; Gallelli, Luca (Current Drug Safety, 2018)
Background: Selective agents able to locate and identify unique targets represent a crucial aspect of modern pharmacology. The exclusive location of Sodium-Glucose co-Transporter-2 (SGLUT2) on kidneys prompt companies to develop SGLT2 inhibitors that today are the latest class of drugs for diabetes treatment. In particular, canagliflozin blocks the re-absorption of glucose in the kidney lowering blood glucose levels by increasing glucose excretion. Case Description: We report a 61-year old woman who developed an intense and severe pruritus during the treatment with canagliflozin. Clinical and laboratory findings excluded the presence of systemic or skin diseases able to induce pruritus. The discontinuation of canagliflozin and the treatment with pioglitazone/metformin fixed combination induced a remission of pruritus. Conclusion: This case emphasizes the need to consider pruritus as a differential diagnosis during the treatment with canagliflozin.
Keywords: SGLT2